2019
DOI: 10.1038/s41467-019-11501-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphing of liquid crystal surfaces by emergent collectivity

Abstract: Liquid crystal surfaces can undergo topographical morphing in response to external cues. These shape-shifting coatings promise a revolution in various applications, from haptic feedback in soft robotics or displays to self-cleaning solar panels. The changes in surface topography can be controlled by tailoring the molecular architecture and mechanics of the liquid crystal network. However, the nanoscopic mechanisms that drive morphological transitions remain unclear. Here, we introduce a frequency-resolved nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(116 citation statements)
references
References 44 publications
9
107
0
Order By: Relevance
“…Thus, based on purely in-plane stimuli an out-of-plane expansion of the LCN is observed. Follow-up experiments by Van der Kooij et al on the same experimental system have since shown that there is a characteristic plasticization time associated with the initial macroscopic deformation of the LCN [36].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, based on purely in-plane stimuli an out-of-plane expansion of the LCN is observed. Follow-up experiments by Van der Kooij et al on the same experimental system have since shown that there is a characteristic plasticization time associated with the initial macroscopic deformation of the LCN [36].…”
Section: Introductionmentioning
confidence: 88%
“…Although one might expect electrothermal or electrostrictive effects to play an important role here, it can be shown that neither can adequately account for the magnitude of the observed modulation [35][36][37][38]. Instead, Liu et al rationalise the observed behavior by remarking that, upon in-plane actuation by the electric field, the end-grafted liquid crystalline mesogens reorient slightly away from their as-prepared homeotropic alignment, increasing their mutual excluded volume with the mesogens that cannot reorient as easily due their incorporation in the background polymer network.…”
Section: Introductionmentioning
confidence: 90%
“…Under the appropriate conditions it translates into macroscopic effects such as mechanical morphing of the coating surfaces. 15 Based on this newly acquired knowledge, in this work we exploit the use of RF AC fields to alter the chemical properties at a coating surface through excreting and absorbing functional liquids. These functional artificial skins may administer medicine (e.g., for wound treatment), adjust tribology by controlled release of lubricants, or carefully dose chemicals for interfacial chemical reactions.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…Under the appropriate conditions it translates into macroscopic effects such as mechanical morphing of the coating surfaces. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Surface oscillation during electrical stimulation has also been revealed with laser speckle imaging in further studies. [ 103,104 ]…”
Section: Switchable Topographies Of Coatings Adhered On Substratesmentioning
confidence: 99%